A novel high-shear and low-pressure grinding method using specially developed abrasive tools. (January 2021) - Tian, Yebing; Li, Linguang; Fan, Shuo; Guo, Qianjian; Cheng, Xiang
In this work, a novel grinding method using a special abrasive tool was first proposed to achieve high tangential grinding force and low normal grinding force. The abrasive tool was developed with flexible composites to remove workpiece materials under "high-shear and low-pressure" grinding mode. The concept of the high-shear and low-pressure grinding method was introduced in detail. Grinding tests were carried out on a precision grinder with the developed abrasive tool for single crystal silicon specimens. The results showed that the grinding force ratio between tangential force and normal force for the proposed grinding method was ranged between 0.9 and 1.3, which was three times larger than that of the conventional grinding method. It was verified that the developed abrasive tool possessed the grinding characteristics of high tangential grinding force and low normal grinding force. After grinding of silicon specimens for 120 min, the value of surface roughness decreased from 429.20 to 32.91 nm under the selected grinding conditions. The surface quality of the silicon specimens was greatly improved after grinding.